Central obesity rather than BMI is associated with chronic pain: A cross-sectional analysis of NHANES - Xu Yang; Xue Yang; Li Yang; Xuemei Dai; Lu Lin; Huaqu Gong; Yinghai Liu; Wei Wu (PLoS ONE, 2025)
Background Chronic pain is a prevalent and debilitating condition that poses a major public health burden. Most existing research on obesity and pain has focused on general obesity, typically assessed using body mass index (BMI). However, BMI fails to capture fat distribution and may not adequately reflect metabolic risks associated with pain. Central obesity, characterized by abdominal fat accumulation, has been increasingly recognized as a more relevant predictor of chronic disease, but its relationship with chronic pain remains underexplored in population-based studies. Methods Data from 2,511 adults in the National Health and Nutrition Examination Survey (NHANES) were analyzed. Weighted logistic regression was used to assess the association between anthropometric indexes, including A Body Shape Index (ABSI), Waist Circumference (WC), Body Roundness Index (BRI), and BMI, and chronic pain. Subgroup and sensitivity analyses were conducted to test robustness. Restricted cubic spline (RCS) was applied to examine nonlinear relationships. Receiver operating characteristic (ROC) analysis compared the predictive performance of the anthropometric indicators. Results Higher ABSI was significantly associated with increased odds of chronic pain, even after adjusting for a wide range of covariates including BMI (adjusted OR for highest vs. lowest quartile: 1.74; 95% CI: 1.16–2.59; P = 0.010). In contrast, BRI, WC, and BMI were not significantly associated with chronic pain. RCS analysis indicated a linear relationship between ABSI and chronic pain. ROC analysis showed that central obesity indicators (ABSI, BRI, and WC) had better discriminative ability than BMI. Findings were consistent across subgroup and sensitivity analyses. Conclusion Central obesity, as measured by ABSI, is significantly associated with chronic pain, independent of BMI and other risk factors. These findings highlight the importance of incorporating central obesity indicators into public health and clinical strategies for chronic pain prevention and management.